CyTOF analysis identifies unusual immune cells in urine of BCG-treated bladder cancer patients - Castellano, Eva; Samba, Célia; Esteso, Gloria; Simpson, Laura; Vendrame, Elena; García‐Cuesta, Eva M.; López‐Cobo, Sheila; Álvarez-Maestro, Mario; Linares, Ana; Leibar, Asier; Ranganath, Thanmayi; Reyburn, Hugh T.; et al. (Frontiers in Immunology, 2022)
High grade non-muscle-invasive bladder tumours are treated with transurethral resection followed by recurrent intravesical instillations of Bacillus Calmette Guérin (BCG). Although most bladder cancer patients respond well to BCG, there is no clinical parameter predictive of treatment response, and when treatment fails, the prognosis is very poor. Further, a high percentage of NMIBC patients treated with BCG suffer unwanted effects that force them to stop treatment. Thus, early identification of patients in which BCG treatment will fail is really important. Here, to identify early stage non-invasive biomarkers of non-responder patients and patients at risk of abandoning the treatment, we longitudinally analysed the phenotype of cells released into the urine of bladder cancer patients 3-7 days after BCG instillations. Mass cytometry (CyTOF) analyses revealed a large proportion of granulocytes and monocytes, mostly expressing activation markers. A novel population of CD15+CD66b+CD14+CD16+ cells was highly abundant in several samples; expression of these markers was confirmed using flow cytometry and qPCR. A stronger inflammatory response was associated with increased cell numbers in the urine; this was not due to hematuria because the cell proportions were distinct from those in the blood. This pilot study represents the first CyTOF analysis of cells recruited to urine during BCG treatment, allowing identification of informative markers associated with treatment response for sub-selection of markers to confirm using conventional techniques. Further studies should jointly evaluate cells and soluble factors in urine in larger cohorts of patients to characterise the arms of the immune response activated in responders and to identify patients at risk of complications from BCG treatment.